Jekel's epidemiology, biostatistics, preventive medicine, and public health - Elmore, J. G. Joann G. (Elsevier Limited, 2020)
Written by renowned epidemiologists and public health experts, this unique text provides complete, concise coverage of epidemiology, biostatistics, preventive medicine, and public health in clear, easy-to-understand terms. One convenient volume delivers must-know content in four complex areas-information that's sure to be covered in today's classrooms and on USMLE exams-presented with a clinical focus and real-life medical examples throughout. Depth of coverage, concise writing style, outstanding online review questions, a clinical emphasis ... these features and more make Jekel's your go-to resource for learning, study, and review.